2019
DOI: 10.1177/0885328219861602
|View full text |Cite
|
Sign up to set email alerts
|

High-strength ceramics as innovative candidates for cardiovascular implants

Abstract: Cytocompatibility and hemocompatibility are essential features for tissue- and blood-contacting implants such as artificial heart valves, vascular grafts and stents. Platelet activation as the main trigger of thrombosis results in implant failures. The purpose of this study results from the demands on anti-coagulant and non-corrosive innovative biomaterials for cardiovascular implants. Therefore, hemocompatibility and cytocompatibility of various high-strength ceramics, such as alumina, zirconia, silicon nitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Viability values indicated that all single crystalline samples are cytocompatible for HUVECs and PBMCs. These results were predicted due to the nontoxic characteristics of polycrystalline Al 2 O 3 and SiC ceramics observed in our previous study, as well as earlier reports. Toxicity of the Triton-X100-treated control surface was already addressed in many studies, which caused total cell destruction for both HUVECs and PBMCs. TX100 causes the disruption of hydrogen bonds within the cell’s lipid bilayer. Thus, the lipid membrane loses its compactness and integrity, which resulted in cell death .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Viability values indicated that all single crystalline samples are cytocompatible for HUVECs and PBMCs. These results were predicted due to the nontoxic characteristics of polycrystalline Al 2 O 3 and SiC ceramics observed in our previous study, as well as earlier reports. Toxicity of the Triton-X100-treated control surface was already addressed in many studies, which caused total cell destruction for both HUVECs and PBMCs. TX100 causes the disruption of hydrogen bonds within the cell’s lipid bilayer. Thus, the lipid membrane loses its compactness and integrity, which resulted in cell death .…”
Section: Discussionsupporting
confidence: 81%
“…As a full activation control (positive control), platelet solution was transferred to an empty 24-well plate. Further steps of the ELISA were described previously by Parlak et al…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Subsequently, the intensity of UV‐marker was measured using Tecan microplate reader at 450 nm. Detailed steps of the ELISA were described previously 26 …”
Section: Methodsmentioning
confidence: 99%
“…ZnO nanoparticles, a FDA recognized biocompatible material, generates NO continuously from endogenous NO donors in blood circulation . It has been shown that some classes of ceramics and glasses, especially monocrystalline silicon carbide, could potentially act as hemocompatible materials for the development of blood-contacting surfaces …”
Section: Implantable Controlled Release Systemsmentioning
confidence: 99%
“…112 It has been shown that some classes of ceramics and glasses, especially monocrystalline silicon carbide, could potentially act as hemocompatible materials for the development of bloodcontacting surfaces. 113 Heparin is one of the anticoagulant agents that has been coated on the surface of 3D printed PLA vascular stents. The in vitro and in vivo findings revealed an inhibition of neointimal hyperplasia, thrombosis, and atherosclerosis (Figure 3d).…”
Section: Implantable Controlled Release Systemsmentioning
confidence: 99%